Effect of Multiple Firings on the Microshear Bond Strength Between a Translucent Zirconia and a Resin Cement - Grangeiro, Mtv [UNESP]; Demachkia, A. M. [UNESP]; Rodrigues, C. S. [UNESP]; Inagati, C. M. [UNESP]; Gonçalves, Nmf [UNESP]; Tanaka, I. V. [UNESP]; Rossi, N. R. [UNESP]; Bottino, M. A. [UNESP] (Operative Dentistry, 2023)
PURPOSE: This study investigated the microshear bond strength between a resin cement and a translucent zirconia subjected to multiple characterization firings. METHODS AND MATERIALS: 5Y-PSZ zirconia blocks (Katana UTML) were sliced, sintered (1550°C, 2 h), and randomly divided into six groups (n=10) according to the number of characterization firings (0, 1, 2, 3, 5, or 10) and aging (baseline or after thermocycling). Each characterization firing was performed at 750°C for 1 minute. The ceramic surfaces were all sandblasted with 50 μm Al2O3 and silanized. Then, cylinders of resin cement (0.96 mm diameter × 2 mm height) were bonded onto their surfaces. The baseline samples were immersed in distilled water for 24 hours before the microshear bond strength (μSBS) tests. The aged samples were tested after 5000 thermocycles in water (5°C-55°C). The failure modes were classified as adhesive, predominantly adhesive, or cohesive. Scanning electron microscope images of the failure modes and the ceramic surfaces after the firings were taken. The μSBS data were analyzed by two-way ANOVA and Tukey's test. RESULTS: The number of characterization firings and aging affected the bond strength. The highest bond strength values were observed from the 2-firing group at baseline. The μSBS results after 1, 2, or 3 characterization firings were similar at baseline and after aging. On the other hand, 0, 5, and 10 firings revealed the lowest bond strengths. The most frequent failures were adhesive and predominantly adhesive. Zirconia grains were not affected by the multiple firings. CONCLUSION: One to three characterization firings after sintering improve the bond strength of 5Y-PSZ to the resin cement when compared to none or several (five or ten) firing cycles.